ANALISIS KELAYAKAN FINANSIAL USAHA AGROINDUSTRI PAKAN IKAN DI KECAMATAN KUOK KABUPATEN KAMPAR (Studi Kasus Usaha Pakan Ikan Bapak Marin) - Lucy Widya Lestari Bintari; Yusmini '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analize the financial feasibility and to analize the level of sensivity of fish feed agroindustry business.This research uses the case study method, the object of the research is a fish feed business in Kuok district Kampar regency. Investment criteria used in analyzing the financial feasibility is Net Present Value (NPV), Internal Rate of Return (IRR) dan Net Benefit Cost Ratio (Net B/C). The results of the research showed that fish feed agroindustry business is feasible to run and developed with the value of NPV as Rp. 3.122.202.366,00(NPV bigger than zero), Net B/C of 2,78 (Net B/C bigger than one) and IRR stay at DF 64% (IRR bigger than DF 12%).The results ofthe sensitivityanalysisshowedthatifthe businesshave a risk from the increases bran prices by 12%, dried fishprice increasesof 12%,a decrease infishfeed production 25% and decline of production time to 23 days in 1 month, then businessisnotsensitive to therisks and the business is worth tobe continued. Resulting risk is not worth the effort, in case sensitivity the increases bran prices by 21,05%, dried fishprice increasesof 26,96%,a decrease infishfeed production34,72% and decline of production time to 13 days in 1 month.   Keywords: Fish Feed Agroindustry, Financial Feasibility, Sensivity